The Coronavirus Disease 2019 Pandemic and Time to Diagnosis for Childhood Pulmonary Diseases: Outcomes of a Tertiary Care Center - Meltem Akgül Erdal; Halime Nayır Büyükşahin; İsmail Güzelkaş; Birce Sunman; Didem Alboğa; Nagehan Emiralioğlu; Ebru Yalçın; Deniz Doğru; H. Uğur Özçelik; Nural Kiper (AVES Yayincilik, 2024)
Objectives: Coronavirus disease 2019 pandemic caused many changes in the social behaviors of individuals and the provision of health systems. Many studies revealed reductions in the number of diagnoses and delays in diagnosis time during the pandemic. This study aimed to evaluate the effect of the pandemic on the time to diagnosis of major diseases of pediatric pulmonology. Materials and Methods: Newly diagnosed patients with cystic fibrosis (CF), childhood interstitial lung disease (chILD), tuberculosis (TB), and primary ciliary dyskinesia (PCD) were grouped into pandemic (group 1) and 2 consecutive pre-pandemic periods divided into equal intervals (groups 2 and 3). For each disease group, the time to diagnosis was compared between the specified periods. Results: A total number of patients were 171 in this study. In the CF group, there was no statistically difference in time to diagnosis between periods. In the chILD group, there was a statistically significant difference in time to diagnosis (P = .036) between groups (group 1: 2 months, group 2: 4 months and group 3: 10.5 months) that was not originated from pandemic period. In TB group there was no statistically significant difference between groups. In the PCD group, the impact of the pandemic on the time to diagnosis could not be clarified because the time interval to diagnosis (minimum: 2 years, maximum: 16 years) exceeded the studied periods (21 months). Conclusion: In our study, no effect found between the pandemic and age at diagnosis or time to diagnosis in patients with PCD, chILD, CF, and TB at our center.